The Distinct Roles of Class I and II RPD3-Like Histone Deacetylases in Salinity Stress Response . Issue 4 (10th October 2017) - Ueda, Minoru; Matsui, Akihiro; Tanaka, Maho; Nakamura, Tomoe; Abe, Takahiro; Sako, Kaori; Sasaki, Taku; Kim, Jong-Myong; Ito, Akihiro; Nishino, Norikazu; Shimada, Hiroaki; Yoshida, Minoru; et al.
Abstract : Deficiency in a class I HDAC (HDA19) suppresses sensitivity to salinity stress induced by deficiencies of class II HDACs. Abstract: Histone acetylation is an essential process in the epigenetic regulation of diverse biological processes, including environmental stress responses in plants. Previously, our research group identified a histone deacetylase (HDAC) inhibitor (HDI) that confers salt tolerance in Arabidopsis ( Arabidopsis thaliana ). In this study, we demonstrate that class I HDAC (HDA19) and class II HDACs (HDA5/14/15/18) control responses to salt stress through different pathways. The screening of 12 different selective HDIs indicated that seven newly reported HDIs enhance salt tolerance. Genetic analysis, based on a pharmacological study, identified which HDACs function in salinity stress tolerance. In the wild-type Columbia-0 background, hda19 plants exhibit tolerance to high-salinity stress, while hda5/14/15/18 plants exhibit hypersensitivity to salt stress. Transcriptome analysis revealed that the effect of HDA19 deficiency on the response to salinity stress is distinct from that of HDA5/14/15/18 deficiencies. In hda19 plants, the expression levels of stress tolerance-related genes, late embryogenesis abundant proteins that prevent protein aggregation and positive regulators such as ABI5 and NAC019 in abscisic acid signaling, were induced strongly relative to the wild type. Neither of these elements was up-regulated in the hda5/14/15/18 plants. The mutagenesis of HDA19 by genome editing in the hda5/14/15/18 plants enhanced salt tolerance, suggesting that suppression of HDA19 masks the phenotype caused by the suppression of class II HDACs in the salinity stress response. Collectively, our results demonstrate that HDIs that inhibit class I HDACs allow the rescue of plants from salinity stress regardless of their selectivity, and they provide insight into the hierarchal regulation of environmental stress responses through HDAC isoforms.